Confidentiality, anonymity and amnesty for midwives in distress seeking online support – Ethical? - Pezaro, Sally (Nursing ethics, 2018)
Background:Midwife health is intrinsically linked to the quality of safe patient care. To ensure safe patient care, there is a need to deliver emotional support to midwives. One option that midwives may turn to may be a confidential online intervention, instead of localised, face-to-face support.Research design:Following the Realist And MEta-narrative Evidence Syntheses: Evolving Standards publication standards, this realist synthesis approach explores the ethical considerations in permitting confidentiality, anonymity and amnesty in online interventions to support midwives in work-related psychological distress. An iterative search methodology was used to select nine papers for review. To assimilate information, papers were examined for ideas relating to ethical dimensions of online interventions to support midwives in work-related psychological distress. This review takes a narrative approach.Findings:Online interventions can support the development of insight, help seeking and open discussion. Additionally, Internet support groups can become morally persuasive in nature. Anonymity and confidentiality are both effective and therapeutic features of online interventions when used in collaboration with effective online moderation. Yet, ethical dilemmas remain where users cannot be identified.Discussion:Confidentiality and anonymity remain key components of successful online interventions. However, sanctioning the corollary component of amnesty may provoke moral discomfort for those seeking immediate accountability. For others, amnesty is seen as essential for open disclosure and help seeking. Ultimately, the needs of midwives must be balanced with the requirement to protect the public and the professional reputation of midwifery.Conclusion:In supporting midwives online, the principles of anonymity, confidentiality and amnesty may evoke some resistance on ethical grounds. However, without offering identity protection, it may not be possible to create effective online support services for midwives. The authors of this article argue that the principles of confidentiality, anonymity and amnesty should be upheld in the pursuit of the greatest benefit for the greatest number of people.